Utilizing ChatGPT as a Pedagogical Tool to Enhance English as a Foreign Language Learners’ Basic English Grammar Competence: A Case Study at an Islamic Boarding School - Sanusi Azhari; Kurniawan Yudhi Nugroho (Journal of Advanced Multidisciplinary Research, 2026)
Mastery of English sentence structure is fundamental yet challenging for EFL learners, forming the basis for effective communication and academic success. In Indonesian Islamic boarding schools, students juggling intensive religious studies and academics often have limited targeted grammar practice, intensifying difficulties with sentence construction. Although ChatGPT shows promise as a pedagogical tool in EFL contexts, prior research has largely examined university students or prolonged interventions, leaving a gap regarding its impact in short-term, intensive programs for senior high school students in boarding school settings. This study assessed ChatGPT’s effectiveness in improving EFL learners’ sentence structure competence. Adopting a one-group pretest-posttest design, 14 tenth-grade male students at an Islamic boarding school in Bogor, Indonesia completed a two-week intervention of daily 60-minute ChatGPT-assisted sessions on simple present tense sentence construction, incorporating guided practice and immediate feedback. Sentence structure competence was evaluated using a 15-item multiple-choice grammar test developed by the researcher, administered before and after the intervention. Results indicated statistically significant gains, with mean scores rising from 68.43 (SD = 25.922) on the pretest to 90.43 (SD = 6.418) on the posttest (mean difference = 22; t(13) = 3.297, p = .006). The Shapiro-Wilk test confirmed normality, and the large effect size underscored substantial practical significance. These findings demonstrate that even brief, intensive ChatGPT interventions can substantially enhance EFL learners’ sentence structure competence. ChatGPT proves a practical, time-efficient, and engaging tool for grammar instruction in Indonesian boarding school contexts. EFL teachers are advised to incorporate structured ChatGPT activities into daily lessons to promote individualized learning and lessen teacher workload. Limitations and avenues for future research are discussed.